The Role of The State in Regulating the Behavior of Firms in The Context of a Pandemic ("Journal "U". Economy. Management. Finance.", 2021)
During periods of economic downturn and crisis, many business entities are under the threat of bankruptcy. During such periods, intervention and support from the State is particularly important and necessary. The article considers measures of state regulation of firms ' activities, including measures to support business during the coronavirus pandemic.
Keywords: economy; pandemic; business entities; state support; tax preferences; financial support